Phosphorus magnetic resonance spectroscopy and imaging (31P-MRS/MRSI) as a window to brain and muscle metabolism: A review of the methods. (July 2020) - Santos-Díaz, Alejandro; Noseworthy, Michael D.
Abstract: Phosphorus magnetic resonance spectroscopy and spectroscopic imaging ( 31 P-MRS/MRSI) non-invasively provide very important information regarding energy metabolism as they can detect high-energy metabolites and membrane phospholipids in vivo. They have repeatedly proven their utility in the study of healthy and disease conditions in skeletal muscle and brain tissue, as many disorders are related to imbalances in bioenergetics processes. However, they are not often used in a clinic setting, as there are technical challenges imposed by the low sensitivity and low concentration of metabolites leading to low signal to noise ratio (SNR), coarse spatial resolution and very long acquisition times. This paper presents an overview of the main techniques used for the acquisition, data reconstruction and processing of 31 P-MRS/MRSI experiments with emphasis in methodological aspects, as well as some of their main applications in the study of skeletal muscle and brain tissue. Also, recent advances in the development of accelerated methods for acquisition of 31 P-MR data are discussed.